Transcending Binariesin Hanif Kureishis Goodbye, Mothers Dichotomous settings - Ali Termizi, Arbaayah; Cheong, Pui Yin (i-Proclaim, 2015)
Hanif Kureishiis often noted for his tendency to pit his protagonist against the dichotomous setting around him. In one of Kureishi’s short stories titled Goodbye, Mother, Harry, the protagonist is placed against the dichotomous physical and spatial settings in the story. This dichotomous physical setting reflects a long time conflict between the urban and the suburban, whereas the spatial one represents the past and the present on opposing sides. Accordingly, these opposing elements also come to represent equally conflicting connotations to the protagonist, in terms of (a) class difference (high class versus middle class), (b) female figures in life (mother versus wife), and (c) generational contrast (previous versus current generation). Thus, this paper intends to elucidate the struggle that Harry goes through as he confronts the three above said elements in relation to the physical and spatial settings in the story. Hence this paper focuses on the relationship between the motif of movement/leaving with freedom as well as looking at the form(s) of victory/freedom that Harry may obtain when (or if) he succeeds while moving between the binaries. The exploration of these themes is guided, primarily, by Raymond William’s concept of ‘social formula’ and John Christman’s extension of Isiah Berlin’s notion of positive/negative freedom. In short, this study proposes that Harry does transcend from one sphere of the binaries to the other, and his movement/leaving has helped to facilitate a positive freedom within him, which culminates, ultimately, in the discovery of his self-knowledge and identity.